Probing the subcutaneous absorption of a PEGylated FUD peptide nanomedicine via in vivo fluorescence imaging - Pawel Zbyszynski; Inger Toraason; Lauren Repp; Glen S. Kwon (Nano Convergence, 2019)
Abstract The Functional Upstream Domain (FUD) peptide is a potent inhibitor of fibronectin assembly and a therapeutic candidate for disorders linked with hyperdeposition of fibronectin-modulated ECM proteins. Most recently, experiments involving subcutaneous (s.c.) administration of a PEGylated FUD (PEG-FUD) of 27.5 kDa molecular weight yielded a significant reduction of fibronectin and collagen deposition in a murine model of renal fibrosis. The benefits of FUD PEGylation need to be studied to unlock the full potential of the PEG-FUD platform. This work studies the impact of PEGylating the FUD peptide with differently sized PEG on its absorption from the site of injection following s.c. delivery using non-invasive in vivo fluorescence imaging. The FUD and mFUD (control) peptides and their 10 kDa, 20 kDa, and 40 kDa PEG conjugates were labeled with the sulfo-Cy5 fluorophore. Isothermal titration calorimetry (ITC) and confocal fluorescence microscopy experiments verified FUD and PEG-FUD fibronectin binding activity preservation following sulfo-Cy5 labeling. Fluorescence in vivo imaging experiments revealed a linear relationship between the absorption apparent half-life (t1/2) and the MW of FUD, mFUD, and their PEG conjugates. Detected drug signal in the kidney and bladder regions of mice suggests that smaller peptides of both the FUD and mFUD series enter the kidney earlier and in higher amounts than their larger PEG conjugates. This work highlights an important delayed dose absorption enhancement that MW modification via PEGylation can contribute to a drug when combined with the subcutaneous route of delivery.